A specific cathepsin-L-like protease purified from an insect midgut shows antibacterial activity against gut symbiotic bacteria. Issue 1 (November 2015) - Byeon, Jin Hee; Seo, Eun Sil; Lee, Jun Beom; Lee, Min Ja; Kim, Jiyeun Kate; Yoo, Jin Wook; Jung, Yunjin; Lee, Bok Luel
Abstract: Because gut symbiotic bacteria affect host biology, host insects are expected to evolve some mechanisms for regulating symbiont population. The bean bug, Riptortus pedestris, harbors the Burkholderia genus as a gut symbiont in the midgut organ, designated as the M4 region. Recently, we demonstrated that the lysate of M4B, the region adjacent to M4, harbors potent antibacterial activity against symbiotic Burkholderia but not to cultured Burkholderia . However, the bona fide substance responsible for observed antibacterial activity was not identified in the previous study. Here, we report that cathepsin-L-like protease purified from the lysate of M4B showed strong antibacterial activity against symbiotic Burkholderia but not the cultured Burkholderia. To further confirm this activity, recombinant cathepsin-L-like protease expressed in Escherichia coli also showed antibacterial activity against symbiotic Burkholderia . These results suggest that cathepsin-L-like protease purified from the M4B region plays a critical role in controlling the population of the Burkholderia gut symbiont. Highlights: Regulation of the gut symbiont population is suggested to be critical for modulation of host biology. A specific host midgut region is reported to exhibit antibacterial activity against symbiotic bacteria. Purified cathepsin-L protease from gut lysate shows antibacterial activity against host gut symbiont. Cathepsin-L-like protease controls the population of the Burkholderia gut symbiont.